Topical metformin suppresses angiogenesis pathways induced by pulsed dye laser irradiation in animal models. Issue 3 (30th September 2021) - Wang, Meiling; Lin, Yan; Shi, Wenhao; Chen, Xuechao; Mi, Zihao; Jia, Zhiwei; Pan, Qing; Wang, Zhenzhen; Han, Jian; Liu, Huaxu
Abstract: Pulsed dye laser (PDL) is the first‐line treatment for port‐wine stain (PWS). However, only a small portion of the lesions could be completely cleared by PDL treatment, which might be related to the regeneration and revascularization of the vascular structures after laser irradiation. Recently, it is believed that the suppression of regeneration and revascularization of photocoagulated blood vessels can achieve a better therapeutic outcome. We use rabbit ear and SD rat as the animal models to investigate whether PDL‐induced angiogenesis can be suppressed by topical metformin. Our results showed that topical application of metformin can effectively suppress the PDL‐induced early stage of angiogenesis via inhibition of the AKT/mTOR/P70S6K pathway in animal models.